MAC 18 FL: a widely grown rice variety in Bolivia with preferred grain appearance and cooking quality - CGIAR Research Program on Rice (2019)
Late cycle (137 days), resistant to rice blast, Helminthosporium, and leaf scalding. Extra-long thin and crystalline with good visual appearance. Yield of whole grain in mill: 59.5% Average irrigation yield with agronomic management 9-10 t.ha-1 In dryland 5-6 t.ha-1 High amylose 31.6%, Low Recommended for irrigation conditions